Molecular Pathology Demonstration of SARS-CoV-2 in Cytotrophoblast from Placental Tissue with Chronic Histiocytic Intervillositis, Trophoblast Necrosis and COVID-19 - David A. Schwartz (Journal of Developmental Biology, 2021)
A subset of placentas from pregnant women having the SARS-CoV-2 infection have been found to be infected with the coronavirus using molecular pathology methods including immunohistochemistry and RNA in situ hybridization. These infected placentas can demonstrate several unusual findings which occur together—chronic histiocytic intervillositis, trophoblast necrosis and positive staining of the syncytiotrophoblast for SARS-CoV-2. They frequently also have increased fibrin deposition, which can be massive in some cases. Syncytiotrophoblast is the most frequent fetal-derived cell type to be positive for SARS-CoV-2. It has recently been shown that in a small number of infected placentas, villous stromal macrophages, termed Hofbauer cells, and villous capillary endothelial cells can also stain positive for SARS-CoV-2. This report describes a placenta from a pregnant woman with SARS-CoV-2 that had chronic histiocytic intervillositis, trophoblast necrosis, increased fibrin deposition and positive staining of the syncytiotrophoblast for SARS-CoV-2. In addition, molecular pathology testing including RNAscope and immunohistochemistry for SARS-CoV-2 and double-staining immunohistochemistry using antibodies to E-cadherin and GATA3 revealed that cytotrophoblast cells stained intensely for SARS-CoV-2. All of the cytotrophoblast cells that demonstrated positive staining for SARS-CoV-2 were in direct physical contact with overlying syncytiotrophoblast that also stained positive for the virus. The pattern of cytotrophoblast staining for SARS-CoV-2 was patchy, and there were chorionic villi having diffuse positive staining of the syncytiotrophoblast for SARS-CoV-2, but without staining of cytotrophoblast. This first detailed description of cytotrophoblast involvement by SARS-CoV-2 adds another fetal cell type from infected placentas that demonstrate viral staining.